Violent video games exposure, aggression, emotional intelligence, and prosocial behaviour among pre-university students of Universiti Kebangsaan Malaysia - Faieza Samat,; Maisarah Rosli,; Aiman Al-Haziq Ahmad Kosnan,; Alin Afina Alias,; Muhammad Izzdihar Mohd Zamri, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2022)
The increase of violent content in video games has become a growing concern among the general public. Violent video game exposure has been argued to negatively impact the mental and social development of its players, especially in adolescence. This study aims to investigate the influence of violent video game exposure on the aggression, emotional intelligence, and prosocial behaviour of the pre-university students of ASASIpintar program, Universiti Kebangsaan Malaysia. Instrument used in this study is the set of questionnaires constituted of three constructs: aggression, emotional intelligence and prosocial behaviour. The questionnaires were distributed online to 93 pre-university students, and the results indicate that about 60% of them were highly exposed to violent video games. Furthermore, the intensity of violent video games exposure significantly promotes to aggression tendencies among students who were engaged in the violent video games. In conclusion, though the level of aggression is low, ASASIpintar students who were engaged in violent video games have the tendency to more aggressive behaviour which in the long run may impact their academic achievement.